Development and validation of a scale to evaluate defoliating caterpillars damage in soybean (Glycine max L.), for South of the province of Cordoba - Boito, Graciela Teresa; Crenna, Ana Cecilia; Giuggia, Jorge Antonio; Giovanini, Diego; Oddino, Claudio; Gerardo, Ulises Abel (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2022)
To develop and validate a diagrammatic logarithmic scale to assess the damage caused by defoliating caterpillars in the soybean crop for the South central of Cordoba, damaged leaflets were collected to obtain the maximum defoliation value. Scanning each leaflet, defoliation percentage was calculated by the software WinFolia. Middle value per each class of a seven classes scale was obtained with DOSLOG. Later 140 leaflets, which actual defoliation was determined by WinFolia, were evaluated by six experienced and six inexperienced raters, with and without using the scale. The precision and accuracy validation was determined by using simple linear regression between actual and estimated defoliation, and reproducibility was determined by regressing the 140 estimations of each rater on the estimations made by every other raters. Without using the scale most raters overestimated defoliation, indicating positive constant deviations for all levels of defoliation and in 9 of 12 raters occurred systematic deviations. Accuracy (-1.74 to 1.39) and precision (0.77 to 0.90) improved significantly with the use of the scale. As well as reproducibility was improved. The diagrammatic logarithmic scale is suitable for assess damage caused by defoliating caterpillars in soybean crops in South-Central region of Cordoba.